Nonviral Direct Conversion of Primary Mouse Embryonic Fibroblasts to Neuronal Cells - Andrew F Adler; Christopher L Grigsby; Karina Kulangara; Hong Wang; Ryohei Yasuda; Kam W Leong (Molecular Therapy: Nucleic Acids, 2012)
Transdifferentiation, where differentiated cells are reprogrammed into another lineage without going through an intermediate proliferative stem cell-like stage, is the next frontier of regenerative medicine. Wernig et al. first described the direct conversion of fibroblasts into functional induced neuronal cells (iNs). Subsequent reports of transdifferentiation into clinically relevant neuronal subtypes have further endorsed the prospect of autologous cell therapy for neurodegenerative disorders. So far, all published neuronal transdifferentiation protocols rely on lentiviruses, which likely precludes their clinical translation. Instead, we delivered plasmids encoding neuronal transcription factors (Brn2, Ascl1, Myt1l) to primary mouse embryonic fibroblasts with a bioreducible linear poly(amido amine). The low toxicity and high transfection efficiency of this gene carrier allowed repeated dosing to sustain high transgene expression levels. Serial 0.5 µg cm−2 doses of reprogramming factors delivered at 48-hour intervals produced up to 7.6% Tuj1+ (neuron-specific class III β-tubulin) cells, a subset of which expressed MAP2 (microtubule-associated protein 2), tau, and synaptophysin. A synapsin-red fluorescent protein (RFP) reporter helped to identify more mature, electrophysiologically active cells, with 24/26 patch-clamped RFP+ cells firing action potentials. Some non-virally induced neuronal cells (NiNs) were observed firing multiple and spontaneous action potentials. This study demonstrates the feasibility of nonviral neuronal transdifferentiation, and may be amenable to other transdifferentiation processes.